2-Phenylbenzothiophene-based liquid crystalline semiconductors. (February 2020) - Zhong, Yu-Jie; Zhao, Ke-Qing; Wang, Bi-Qin; Hu, Ping; Monobe, Hirosato; Heinrich, Benoît; Donnio, Bertrand
Abstract: We report herein the design and synthesis of some novel liquid crystalline semiconductors constructed from a biologically and pharmacologically active building block molecule, namely 6-methoxy-2-(4-methoxyphenyl)benzo[b]thiophene, presenting efficient luminescence and medium charge mobility rate. A first series of mesogenic 2-phenylbenzothiophene derivatives ( n PBT) was simply and rapidly obtained in good yields by successive demethylation/alkylation reactions of the available methoxy precursor. The further stepwise oxidations moreover resulted in two new sets of the corresponding sulfoxide ( n PBTO) and sulfone ( n PBTO2 ) derivatives, respectively, that were also mesomorphic. The liquid crystalline behaviour was comprehensively characterized by DSC, POM and SAXS: all compounds exhibit smectic-like behaviour in agreement with their calamitic shape. More specifically, mesogens n PBT showed a SmA phase, with in addition, a higher ordered smectic phase at lower temperature. As for the oxidized mesogens, they displayed a SmA phase only, and over particularly large temperature ranges for the n PBTO with longer chain lengths ( n ≥ 8). The photo-physical properties have also been studied both in solution and thin films, and the molecules were found to display strong absorption in the UV/vis domain and intense luminescence in the range of 400–650 nm (yellowish green light) in high quantum yields (up to 62%). Both absorption and luminescence were also found to be affected by the oxidation of the benzothiophene moiety. Finally, the semi-conducting behaviour of three PBT compounds in the various mesophases was investigated by photocurrent TOF technique. Hole mobility rates of ca. 4 × 10 −3 cm 2 V −1 s −1 were measured in the lower temperature ordered mesophase for all of them, with the best performances (temperature range and mobility values) however obtained for the shortest homolog ( n = 6). With such highly reasonable mesomorphic, light-emitting and semiconducting functional features, as well as being cheap and easy to synthesize and to process, these materials become very attractive and may be incorporated into various kinds of electronic devices (OFET and OLED). Graphical abstract: Image 1 Highlights: New mesomorphous phenylbenzothiophene derivatives were synthesized in two steps from a cheap and abundant precursor. They display photoluminescence in mid-to-high quantum yields. They exhibit smectic mesophase. Charge transports measured by time-of-flight technique are in the 10 −3 cm V −1 s −1 range.